Improving Critical Thinking Skills of High School Students in Physics Learning with Smartphone-Simulation Assisted Inquiry Model - Rahmatta Thoriq Lintangesukmanjaya; Akhmad Iswardani; Binar Kurnia Prahani; Budi Jatmiko; Zainul Arifin Imam Supardi; Dwikoranto (Universitas Negeri Surabaya, 2025)
Objective: Research to describe the improvement of students' critical thinking skills with the Smartphone-Simulation assisted inquiry learning model. Method: This research employed a quantitative descriptive approach, utilizing the data collected. Primary data were obtained from the results of skills tests, observations of learning implementation, and student responses. Furthermore, secondary data was obtained from a literature review to support the primary data. Results: The smartphone simulation media-assisted inquiry model has a positive effect on improving students' critical thinking skills, with an N-Gain score of 0.675. The inquiry learning model, combined with critical thinking, is closely related, focusing on high-level thinking processes that are systematic, reflective, and experience-based. Novelty: Dynamic visualization through the use of smartphone simulations greatly helps improve students' critical thinking skills, accelerating and strengthening the development of their critical thinking in real terms. This is achieved through information transfer and the construction of understanding through active and reflective thinking processes. It is hoped that this research can be one of the implementations of innovative learning planning assisted by digital media.